2015
DOI: 10.1371/journal.pone.0138235
|View full text |Cite
|
Sign up to set email alerts
|

Derepression of Mineral Phosphate Solubilization Phenotype by Insertional Inactivation of iclR in Klebsiella pneumoniae

Abstract: The mode of succinate mediated repression of mineral phosphate solubilization and the role of repressor in suppressing phosphate solubilization phenotype of two free-living nitrogen fixing Klebsiella pneumoniae strains was studied. Organic acid mediated mineral phosphate solubilization phenotype of oxalic acid producing Klebsiella pneumoniae SM6 and SM11 were transcriptionally repressed by IclR in presence of succinate as carbon source. Oxalic acid production and expression of genes of the glyoxylate shunt (ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 49 publications
1
3
0
Order By: Relevance
“…Divya et al (2011) showed that succinate and malate individually and as mixtures repressed gluconate production and PS in Pseudomonas aeruginosa. It is also a component that represses PS phenotype in Klebsiella pneumoniae (Rajput et al, 2013(Rajput et al, , 2015. Based on that and our findings, the reduction of the metabolic flux toward the TCA cycle might be one strategy utilized by SBR5 to perform PS.…”
Section: Discussionsupporting
confidence: 59%
“…Divya et al (2011) showed that succinate and malate individually and as mixtures repressed gluconate production and PS in Pseudomonas aeruginosa. It is also a component that represses PS phenotype in Klebsiella pneumoniae (Rajput et al, 2013(Rajput et al, , 2015. Based on that and our findings, the reduction of the metabolic flux toward the TCA cycle might be one strategy utilized by SBR5 to perform PS.…”
Section: Discussionsupporting
confidence: 59%
“…E. cloacae was found to release an appreciable amount of IAA (74.2 μg/mL) after 120 h of incubation, which was induced by L -tryptophan (50 mM). Otherwise, the K. pneumoniae strain was a low auxin producer (0.328 μg/mL); this concentration is much lower compared to those reported in rhizospheric and free-living strains of K. pneumoniae (Sachdev et al, 2009; Rajput et al, 2015; Kuan et al, 2016).…”
Section: Discussionmentioning
confidence: 67%
“…As shown in Table 1, E. cloacae and K. pneumoniae have phosphate solubilization indices of 148.59 ± 5.38 and 131.11 ± 7.84, respectively. Congruently, both genera have been previously reported to be phosphate solubilizers (Rajput et al, 2015; Dhole et al, 2016; Shabanamol et al, 2018; Zheng et al, 2018). The production of phytohormones such IAA is another factor influencing plant growth.…”
Section: Discussionmentioning
confidence: 99%
“…was higher in the media of AlPO 4 than other P sources [ 35 ]. The PSF secretes various organic acids, such as malic, gluconic, tartaric, oxalic, citric and butyric et al [ 36 , 37 ]. Li et al found oxalic acid was the main product during FePO 4 and AlPO 4 solubilization by Aspergillus spp., whereas gluconic acid was mainly produced by Penicillium spp.…”
Section: Discussionmentioning
confidence: 99%